Exploring mixed reality based on self-efficacy and motivation of users - Kathy Essmiller; Tutaleni I. Asino; Ayodeji Ibukun; Frances Alvarado-Albertorio; Sarinporn Chaivisit; Thanh Do; Younglong Kim (Association for Learning Technology, 2020)
This study addresses the question of how to facilitate instruction and practice with virtual reality to mitigate the detrimental impact of cognitive load associated with use in simple procedural tasks. The study collected data from 63 college students aged 18 years and above from a university in the southern part of the USA. Each study participant completed a questionnaire that consisted of 22 questions using a seven-point Likert scale. The results show that there are no significant differences between motivation and self-efficacy as it relates to three selected activities: Roboraid, Tutorial and Freeplay. The opportunity for meaningful learning through the use of the mixed reality is enticing; there is value in exploring facilitation of these learning opportunities through redistribution of cognitive load.